Association of Workplace Bullying and the Quality of Nursing Care in Intensive Care Unit and Emergency Department Nurses - F Hajibabaee; SH Mousavi; A Hosseini; SH Haghani; S Bahramali (Iran University of Medical Sciences, 2020)
Background & Aims: The work environment of healthcare providers and hospitals is constantly exposed to tremendous work pressure, complexity, and chaos. Due to the changes in various fields of treatment and care, these work environments are constantly changing as well. Meanwhile, bullying is considered to be a serious phenomenon in these organizations, which has also been reported worldwide as an important issue in the nursing profession. Workplace bullying could variably affect nursing. In healthcare organizations, workplace bullying could increase absenteeism, job loss, and job dissatisfaction among the employees. Furthermore, this phenomenon may reduce the quality of nursing care in hospitals and medical centers. These issues are particularly highlighted in the nursing profession since as the largest group of healthcare providers in these organizations and the leading managers of hospitals, nurses play a pivotal role in patient care. Improving the quality of nursing care is the most important factor to accelerate the recovery and return of patients to the community; therefore, the quality assessment of nursing care is essential. In Iran, most of the studies on bullying have been performed on students and teachers in schools, and few studies have been focused on nurses. Given the lack of accurate statistics on the rate of workplace bullying among Iranian nurses and the fact that the quality of nursing care is an important issue that could be affected by the bullying phenomenon, the present study aimed to evaluate the level of workplace bullying among Iranian nurses and its association with the quality of nursing care. Materials & Methods: This cross-sectional, descriptive-correlational study was conducted on 200 emergency department and intensive care unit (ICU) nurses at Imam Khomeini Hospital Complex affiliated to Tehran University of Medical Sciences, Iran in 2019. The sample size included 200 nurses who were selected via simple random sampling. The inclusion criteria were employment as a nurse in the emergency department or ICU of Imam Khomeini Hospital Complex, willingness to participate in the study, and minimum work experience of six months as a nurse in the department. The exclusion criterion was incomplete questionnaires. Data were collected using a demographic questionnaire (age, gender, marital status, admission to the nursing major based on interest/knowledge, education level, clinical ward, service history, type of employment, shift work, duration of employment in the current department, having a managerial position, interest in the workplace, and coercion in the current department), negative acts questionnaire-revised, and SERVQUAL questionnaire. Sampling was performed after the approval of the study protocol and receiving the ethics license from the Joint Organizational Ethics Committee of the School of Nursing and Midwifery and the School of Rehabilitation of Tehran University of Medical Sciences. Eligible nurses were selected after explaining the research objectives and procedures and being assured of the confidentiality of their information with oral consent. The questionnaires were completed anonymously and in a self-report manner. Data analysis was performed in SPSS version 16 using descriptive statistics to describe the samples (frequency distribution tables, mean, and standard deviation). In addition, research objectives were used to describe the samples. To determine the gap between the perceptions and expectations regarding the quality of nursing care, paired t-test was used, and to determine the correlation between workplace bullying and the quality of nursing care, Pearsonchr('39')s correlation-coefficient was employed at the significance level of 0.05. Results: About half of the nurses (51.5%) were female, with the mean age of 32.58 ± 6.38 years. The mean work experience of the subjects was 9.74 ± 5.86 years in the nursing profession and 4.59 ± 3.99 years in their current ward of employment. The majority of the nurses (51%) were formally employed, had rotating work shifts (77%), and worked in the ICU (61.5%). In addition, most of the nurses had a BSc degree (84.5%). Based on the experience of daily or weekly workplace bullying, the mean workplace bullying of the nurses in the work-related bullying dimension was 10.11%, while it was 4.27% in the person-related dimension, and 5.66% in the physical dimension, with an overall mean of 6.68%. The maximum and minimum mean values belonged in the dimensions of work-related bullying and physical dimension, respectively. The results of paired t-test indicated significant differences between the dimensions of the perceptions, expectations, and gaps in the quality of nursing care in the viewpoint of the nurses and the dimensions of reliability (P<0.001), assurance (P<0.001), and total score (P<0.001). Furthermore, workplace bullying had inverse, significant correlations with the dimensions of reliability (P=0.006; r=-0.194) and assurance of nursing care quality (P=0.001; r=-0.229), so that with decreased workplace bullying, the quality of nursing care increased in these dimensions. Conclusion: Although the results of this study indicated the low prevalence of bullying among nurses, nursing managers and policymakers should properly plan for the recognition, prevention, and management of this phenomenon due to the physical, psychological, and organizational effects of workplace bullying on the nurses employed in hospitals and health centers. Moreover, the organizational factors that lead to the workplace bullying of nurses should be identified. Due to the significant associations between workplace bullying and the dimensions of the reliability and quality assurance of nursing care, hospitals must fulfill their promises accurately and consistently. By recruiting nurses with adequate knowledge and skills, a sense of trust and confidence should be created in patients. This study showed that the lower rate of workplace bullying is associated with the higher quality of nursing care. Therefore, it is recommended that further investigations be focused on the effects of workplace bullying on patient care and its dimensions, as well as the quality of the provided care in hospitals and health centers.